2002
DOI: 10.1159/000056195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nipradilol on Alpha-Adrenoceptor Function in Ocular Arteries

Abstract: The effects of nipradilol, a drug used in the treatment of glaucoma, on the contractions induced by noradrenaline and phenylephrine in isolated dog central retinal, external and internal ophthalmic arteries and pig ciliary arteries were investigated. In dog ocular arteries treated with oxyhemoglobin (1.6 × 10–5 mol/l) to adsorb nitric oxide, noradrenaline (2 × 10–8 to 10–5 mol/l) produced a concentration-related contraction which was markedly inhibited by prazosin but not by yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In patients with schizophrenia and visual disturbance, deterioration of the visual cortex and retinal thickness was discovered within three years of the patients beginning to take an antipsychotic agent [32]. Other scholars reported that cystoid macular edema induced by risperidone may be caused by, for example, the agent directly affecting the retinal vascular endothelium or vasorelaxation through alpha-adrenergic blockade [33]. Thus, whether clozapine affects the retina should be investigated, and the possible mechanism should be identified.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with schizophrenia and visual disturbance, deterioration of the visual cortex and retinal thickness was discovered within three years of the patients beginning to take an antipsychotic agent [32]. Other scholars reported that cystoid macular edema induced by risperidone may be caused by, for example, the agent directly affecting the retinal vascular endothelium or vasorelaxation through alpha-adrenergic blockade [33]. Thus, whether clozapine affects the retina should be investigated, and the possible mechanism should be identified.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that nipradilol increases ophthalmic circulation by direct activity on retinal vessels, and the activity is based on blocking the alpha 1 ‐receptor, which has been shown in cats, monkeys and humans 9,12,17 . In dogs it is reported that nipradilol extends vessels in vitro 19 . Thus, we expect that nipradilol increases ocular circulation in dogs.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, ophthalmic circulation has been considered in the treatment of glaucoma 17–19 . It is reported that nipradilol increases ophthalmic circulation by direct activity on retinal vessels, and the activity is based on blocking the alpha 1 ‐receptor, which has been shown in cats, monkeys and humans 9,12,17 .…”
Section: Discussionmentioning
confidence: 99%
“…These include a high affinity for serotonin receptors, a1-adrenergic and a2-adrenergic receptor blockade, and dopaminergic receptor blockade [5]. Research suggests that mechanisms such as vasorelaxation via alpha adrenergic blockade or direct effects on the retinal vascular endothelium may be responsible for risperidone-induced CME [6].…”
Section: Discussionmentioning
confidence: 99%